PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN MUBA ELECTRIC POWER - Edy Agusno, Bambang; Choiriyah, Choiriyah (Universitas muhammadiyah palembang, 2012)
This research was done to investigating the impact of compensation, work enviroment, and leadership style on performance PT Muba Electric Power. This research using descriptive-verificate survey design. The variables in this research are compensation, enviroment work, leadership style, and performance of employees. The analysis of this research is employees performance of multiple regression analysis. The result described that the coefficient correlation (R) is 0.801. The independent variables integratively could describe the dependent variables with the contribution is 64,2%. Besides, the value of F is 4,210 which is significant. It can be conclude that compensation, enviroment work, and leadership style have an impact on performance of employees PT Muba Electric Power.